Laparoscopic Sacrocolpopexy for Beginners How to Start if you Never Dared Before? - von Theobald, Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book offers a practical surgical guide, helping surgeons learn the technique needed to perform Laparoscopic SacroColpoPexy (LSCP). To do so, it explains the surgical process in straightforward language, supplemented by images and diagrams, while also discussing why this procedure is so effective. The book has two primary goals: to provide those surgeons who have never performed LSCP before with essential insights and technical expertise, based on the author$1 (Bs 20 years of practical surgical experience; and to allay the common fear of possible complications. Following a 2012 FDA warning, surgeons whose work involved vaginal prolapse repair have been looking for an alternative technique. Though LSCP offers a safe alternative to current methods, the available literature on it is sparse. This book provides a comprehensive guide to the techniques and methods needed by surgeons operating on pelvic organ prolapse in a range of different specialties, including urogynecology, urology, and gynecology.s
1. Historical aspects -- 2. Physiopathology of POP -- 3. Anatomy -- 4. Operative technique -- 5. Debate: hysterectomy or not? -- 6. Debate: SUI operation associated or not? -- 7. How to start with LSCP when you$1 (Bre a beginner? -- 8. Tricks and tips: how to make a long story short? -- 9. Short and long term results : what can you expect following LSCP -- 10. How to select patients to improve results? -- 11. Post operative care -- 12. Alternative techniques: which and when? 13. Historical aspects.s
Keywords: Medicine; Gynecology; Surgery; Urology; Medicine & Public Health; Surgery; Gynecology; Urology